Aplicações estratégicas de nanocompósitos multifuncionais de óxido de grafeno reduzido e hexacianoferratos bimetálicos: da construção de sensores eletroquímicos à conversão e armazenamento de energia - Borges, Pedro Henrique de Souza (2024)
This thesis addressed the synthesis of nanomaterials based on reduced graphene oxide (rGO) and bimetallic hexacyanoferrates (bMHCF) via electrochemical route. The influence of the varied parameters was statistically analyzed aiming at different applications. The syntheses were performed in two steps by cyclic voltammetry: in the first step, the proportion of metallic precursors was evaluated, and in the second step, the pH of the ferricyanide solution was evaluated to form the hexacyanoferrates. For the first proposed material, a novel nanocomposite of reduced graphene oxide with copper and silver hexacyanoferrate (rGO/AgCuHCF) was prepared and used as an electrochemical sensor for nicotine determination. The method using the material exhibited linear behavior in two regions: 5.0 – 100.0 and 100.0 – 2000.0 μmol L-1, with detection (LOD) and quantification limits (LOQ) of 1.5 and 4.9 μmol L-1, respectively. The sensor also showed repeatability (n = 10) and reproducibility (n = 4) values with relative standard deviations of 1.33% and 7.50%, respectively. Two types of commercial tobacco samples, cigarette and straw, were analyzed, revealing a calculated t-value of 0.26, lower than the critical t-value of 2.78 in the two-tailed analysis, confirming the reliability of the method. Additionally, an rGO/CoNiHCF nanocomposite was prepared, acting as a precursor catalyst for the oxygen evolution reaction (OER). It was found that, in alkaline medium and after 10 hours, rGO/CoNiFeOOH exhibited superior stability (an increase of only 4.23% from the initial potential) compared to one of the materials considered state-ofthe-art by the scientific community for this purpose, RuO2 (an increase of 26.59% from the initial potential). Furthermore, it was observed that the presence of rGO supporting the catalytic agents in CoNiFeOOH is essential to preserve its stability, as its absence leads to an increase of 19.20% in the required initial potential. Finally, a synthesis route for a novel rGO/CoAgHCF nanocomposite was demonstrated for use in supercapacitor components. It exhibited predominant diffusional current showing lower contribution from surface-controlled processes. Charge/discharge tests revealed a specific capacitance of 182.6 F g-1 at a current density of 0.1 A g-1 for rGO/CoAgHCF between 0.4 and 0.9 V. The compounds synthesized in this work proved to be multifunctional materials applied in strategic areas such as sensing, conversion, and energy storage.